C-alkylation reactions catalyzed by silica-supported Keggin heteropolyacids - Pizzio, Luis Rene (2005)
Aromatic alkylation reactions were studied using molybdophosphoric and tungstophosphoric acids supported on silica as catalysts. Benzene and toluene alkylation was carried out with benzyl chloride or benzyl alcohol. Also, cyclohexene and cyclohexanol were used as alkylating agents of toluene. These catalysts allow quantitative conversions in short times, with very good yields in monoalkylation products and minimal formation of polyalkylation products. Regioselectivity in these reactions is similar to that described in literature for different catalysts but the latter are markedly less efficient. In the reaction of formal [3 + 2] cycloaddition with benzyl alcohols catalyzed by silica-supported molybdophosphoric acid, the results are similar to those previously obtained using SnCl4 as catalyst.